Food insecurity and COVID-19-related experiences among people with HIV: A mixed methods analysis and conceptual framework - Dini Harsono; Kelsey Sklar; Michael Silver; Mayange Frederick; Merceditas Villanueva; E. Jennifer Edelman; Jessica E. Yager (PLoS ONE, 2026)
Food insecurity is a key driver of health disparities in the United States and globally, and is associated with increased likelihood of chronic diseases and poorer health outcomes. Social and economic disruptions during the COVID-19 pandemic increased the level of food insecurity and disproportionately impacted low-income households and racial and ethnic minority groups. In this mixed methods study, we explored relationships between sociodemographic factors, HIV care engagement, and experiences of food insecurity in people with HIV (PWH) during the first wave of the COVID-19 pandemic. We administered a one-time telephone survey to PWH engaged in two HIV clinics in the U.S. Northeast (n = 283) and conducted four focus groups with clinical staff (n = 23). Among the surveyed PWH, 30.7% (n = 87) reported experiences of food insecurity early in the COVID-19 pandemic. Receiving care in Brooklyn, NY, being unemployed prior to the pandemic, and experiencing some or a lot of changes in daily routine due to the pandemic were associated with food insecurity experiences. Qualitative analysis of patients’ free-text survey responses and clinical staff focus group transcripts identified factors at individual, intrapersonal, community, and structural levels contributing to food insecurity experiences during the pandemic. Informed by the findings, we developed a conceptual social-ecological framework illustrating the linkages between experiences of food insecurity and COVID-19 among PWH. Efforts to address food insecurity among PWH should include screening for food needs in HIV care settings, communicating about food assistance resources and programs, and implementing evidence-based interventions that can improve food security and nutrition.